2020
DOI: 10.5334/joc.108
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Failure to Produce a Cognitive Load Effect in Visual Working Memory Using a Standard Dual-Task Procedure

Abstract: Working memory performance is impaired when an attention-demanding task is executed during memory retention. The cognitive load effect is the consistent finding that the size of the memory impairment is determined by the relative amount of time that the secondary processing task occupies attention during memory retention. Cognitive load has been proposed to be a Priority-A benchmark any model of working memory should be able to explain (Oberauer et al., 2018), in part because the effect appears to generalize a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 37 publications
1
15
1
Order By: Relevance
“…Contrary to our expectations, we found evidence against the effect of CL. If this absence of effect is confirmed, faces could be added to the list of visuospatial materials that proved to be immune to CL manipulations (Ricker & Cowan, 2010;Ricker & Vergauwe, 2020;Vergauwe, Camos & Barrouillet, 2014). Finally, we found weak evidence against the interaction between CL and face ethnicity, going against our hypothesis.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Contrary to our expectations, we found evidence against the effect of CL. If this absence of effect is confirmed, faces could be added to the list of visuospatial materials that proved to be immune to CL manipulations (Ricker & Cowan, 2010;Ricker & Vergauwe, 2020;Vergauwe, Camos & Barrouillet, 2014). Finally, we found weak evidence against the interaction between CL and face ethnicity, going against our hypothesis.…”
Section: Discussionmentioning
confidence: 51%
“…To conclude regarding attentional refreshing, previous studies have reported that some materials were not influenced by CL manipulations. They were always in the visual domain, but concern mainly uncommon memoranda (e.g., fonts, unconventional characters, positions around a circle; Ricker & Cowan, 2010;Ricker & Vergauwe, 2020;Vergauwe, et al, 2014). This has led researchers to suggest that, to be unrefreshable, memoranda should have little or no prior representation in LTM (Ricker & Vergauwe, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 16 stimuli per category. For the spatial category, there were 16 positions that a rocket could occupy on a circular display; based on the memory items from Ricker and Vergauwe (2020). For the visual category, there were 16 images of robots (generated by typing the following numbers into the 'generate' query space at Robohash.org: 10,20,30,40,50,60,70, were 16 images of random nonwords generated by WinWordGen 1.0 (Duyck et al, 2004).…”
Section: Stimulimentioning
confidence: 99%
“…Imposing tasks that demand attention during the retention interval hinders VWM performance (Allen et al, 2006;Brown & Brockmole, 2010;C. C. Morey & Bieler, 2013), and more so the more attentionally demanding the task is (Loaiza & Souza, 2019;Souza & Oberauer, 2017;Vergauwe et al, 2014; but see Ricker & Vergauwe, 2020). However, the notion that sustained attention is necessary for VWM maintenance is being challenged by other studies demonstrating that performance decrements occur in some dual-task conditions but not others (Hollingworth & Maxcey-Richard, 2013;Lewis-Peacock et al, 2011;Olivers et al, 2011;Rerko et al, 2014;Wang et al, 2018Wang et al, , 2019.…”
Section: The Role Of Attention For Encoding Maintenance and Retrievalmentioning
confidence: 99%